EFFECT OF ARTIFICIAL INTELLIGENCE ON TERTIARY INSTITUTIONS IN NIGERIA: A CRITICAL ANALYSIS - SULEIMAN , MARYAM (Int’l Journal of Education Research and Scientific Development, 2024)
This study is a descriptive survey design that investigated the effect of Artificial Intelligence (AI) on tertiary institutions in Nigeria. The population of the study is the total number of staff in all the tertiary institutions in Sokoto State of Nigeria. The respondents were the 1612 comprising of 530 academic staff and 1082 non-academic staff of the institutions that were sampled using the stratified random sampling. Two specific objectives, research questions and one null hypothesis were postulated to guide this study. The researcher structured a four Likert scale questionnaire titled Artificial Intelligence and Tertiary Education in Nigeria (AITEN) to elicit information from the respondents. The questionnaire was validated by expert judgement of three academic authorities; two from the department of computer science and one from educational measurement and evaluation and the reliability index was 0.79 using the Person Product Correlation coefficient formula (r). The mean and standard deviation were used in answering the research questions while the hypotheses were tested by the z-test statistical tool at 0.05 level of significance. The findings reveal that personalized learning, improved management efficiency, enhanced student engagement, innovation and competitive advantage, enhanced faculty productivity, and optimized administrative processes ere the effects of adopting AI in tertiary institutions in Nigeria. Nevertheless, the study highlights the need for strategic planning, infrastructure development, and capacity building to ensure effective AI adoption and mitigate its negative consequences.